Maximizing Quality of Life in Children with Epilepsy - Yu-Tze Ng (MDPI AG, 2022)
Arguably significant progress and improvement in the medical and surgical treatments of seizures and epilepsy in children have occurred; however, there have been relatively fewer efforts in optimizing the care of lifestyle complications related to the disease state. Many patients have significant behavioral and mental health comorbidities, including ADHD (attention deficit hyperactivity disorder), which should be treated. After epilepsy surgery, only seizure freedom results in improved quality of life (QOL). Improved compliance leads to better seizure control and ensuring that caregivers have a rescue treatment helps empower patients. Education and improving seizure illness perception is beneficial. Cannabidiol may have benefits other than seizure control. The majority of children are mainly concerned about the stigma attached to having epilepsy. Driving affecting older children is discussed. Restrictions on these children should be minimized and enabling regular activities maximized.